Rekontekstualisasi metode dakwah Walisongo: Studi komparatif Sunan Kalijaga, Sunan Bonang, dan Sunan Giri di era digital - Septiana, Nur Ayu (Maliki Interdisciplinary Journal, 2026)
The spread of Islam in Java cannot be separated from the adaptive and contextual da’wah strategies of Walisongo. This article aims to analyze and compare the da’wah methods of Sunan Kalijaga, Sunan Bonang, and Sunan Giri, as well as their relevance in addressing contemporary challenges in the digital era. This study employs a qualitative descriptive approach through literature review of historical sources and recent scholarly works. The findings indicate that Sunan Kalijaga emphasized cultural da’wah through arts and local symbols, Sunan Bonang developed a Sufi-oriented approach using music and literary traditions, while Sunan Giri focused on institutional da’wah through structured education and cadre formation. These approaches were effective as they accommodated Hindu-Buddhist and animistic traditions without generating social conflict. In the digital context, Walisongo’s da’wah models remain relevant when adapted into creative cultural content, digital religious education, and spiritual reinforcement to counter radicalism, misinformation, and hedonistic lifestyles. This study concludes that Walisongo’s da’wah represents not merely a historical legacy but a foundational framework for developing a modern, moderate, inclusive, and contextual Islamic da’wah model.